EMERGENCY ONLINE TEACHING: EARLY CHILDHOOD EDUCATION LECTURERS' PERCEPTION OF BARRIER AND PEDAGOGICAL COMPETENCY - Syaiputra Wahyuda Meisa Diningrat; Meyga Agustia Nindya; Salwa Salwa (Jurnal Cakrawala Pendidikan, 2020)
In this COVID-19 situation, online learning has been widely implemented in higher education contexts. This issue inspires the researchers to conduct further study on barriers encountered by lecturers in higher education. This study was carried out to explore how the lecturers perceive the barriers in online teaching practices and the level of pedagogical competencies perceived by the lecturers in conducting online learning in this emergency. The study employed a cross-sectional survey research design. Data were collected from 73 early childhood education lecturers from four regions in East Java, Indonesia. The questionnaires were developed to measure lecturers' perceptions of barriers in online teaching practices adopted from the TIPEC framework and measure the lecturers' pedagogical competencies. Multivariate analysis of variances was used to analyze the data. The results showed that limited bandwidth, connectivity, and security were the first significant barriers perceived by early childhood lecturers. Meanwhile, the second barriers are related to student lack of engagement and lack of feedback. Then, third barriers are computer viruses, the quality of course content, and reliability of the online assessment instrument. ANOVA results showed that there were significant differences between gender and technological factors, gender and instructional design factors, as well as educational qualification and strategy implementation of factors.